Impact of low-level tannin supplementation on enteric methane emissions, estimated nitrogen excretion, oxidative stress, and animal performance in organic dairy heifers - Schilling, Ashley, author; Stackhouse-Lawson, Kim, advisor; Place, Sara, committee member; Pinedo, Pablo, committee member; Velez, Juan, committee member; Moore-Foster, Rhyannon, committee member (Colorado State University. Libraries, 2023)
Heightened attention and concern regarding the role of anthropogenic greenhouse gas (GHG) emissions in climate change has challenged every industry to reduce their environmental impact. In cattle production systems, the importance of feeding the growing human population while minimizing environmental impacts has been given significant attention throughout the 21st century (Steinfeld et al. 2006; Golub et al., 2012; Eisler et al. 2014). In 2020, the United States dairy industry was responsible for approximately 1.4% of total anthropogenic GHG emissions (EPA, 2021). The GHGs with the largest global warming potential (GWP) equivalents in dairy cattle production systems are nitrous oxide (N2O) and methane (CH4) (Rotz et al., 2021). The use of tannins as a feed additive in cattle production systems has been explored as a GHG mitigation strategy given their potential to reduce enteric CH4 and reactive-nitrogen (N) emissions, while also benefiting animal health. Tannins are secondary components of plants comprised of phenolic compounds of diverse molecular weights and of variable complexity (Place et al., 2011). They are classified into two major classes: 1) hydrolysable and 2) condensed tannins and exhibit variable affects depending on their class, concentration/purity, dose, type, and other factors such as animal species, animal physiological state, and diet composition (Makkar 2003; Aboagye and Beauchemin, 2019). When fed to ruminants, such as dairy cattle (Bos taurus), tannins act as rumen modifiers by altering protein and carbohydrate degradation in the rumen. Moreover, tannins have demonstrated anti-microbial, anti-parasitic, antioxidant, anti-inflammatory, and anti-viral effects in animals and the ability to serve as a bloat control mechanism (Mangan, 1988; Jones et al., 1971, Min et al., 2005). Since tannins target rumen microbial populations that assist in fiber degradation, unintended consequences can include reductions in feed intake, digestibility, and rate of BW gain when tannins are supplemented at concentrations greater than 55 g condensed tannins/kg dry matter (DM) (Min et al., 2003). Therefore, the objective of this study was to determine the impact of low-level tannin (< 0.30 g/kg DMI) supplementation on enteric CH4 emissions, estimated N excretion, oxidative stress, and performance in organic Holstein heifers. Heifers (n=20) were supplemented with Silvafeed® ByPro, a Schinopsis lorentzii condensed tannin product, at increasing levels as recommended by the manufacturer: 0% (CON), 0.075% (LOW), 0.15% (MED), and 0.30% (HIG) of dry matter intake (DMI). Based on animal success to a 28 d acclimation period, 20 certified organic Holstein heifers (BW = 219 ± 17 kg) were randomly assigned into one of the four treatment groups and stratified based on initial body weight (i.e., a completely randomized design). A 7 d pretrial gas analysis was performed prior to study initiation to account for individual animal emission differences. Daily, heifers were supplemented with one kg of sweet feed and tannin in accordance with the assigned treatment in individual feeding stanchions for 45 d and fed a basal total mixed ration (TMR) diet through four SmartFeed Pro intake measurement bunk systems (C-Lock Inc., Rapid City, SD) which allowed for measurement of individual animal feed intake. Additionally, CH4 and carbon dioxide (CO2) production was measured using one GreenFeed automated head chamber system (AHCS, C-Lock Inc., Rapid City, SD) for the entirety of the study. Statistical analysis was conducted in R© (R Core Team, 2021, v. 4.1.2). Data were analyzed as a completely randomized design with animal (n=20) as the experimental unit, using the Type III ANOVA procedure. Post-hoc pairwise comparisons for dependent variables by treatment were performed using the least squared means procedure with the Tukey HSD adjustment applied. Daily CH4 production ranged from 136.5 to 140.1 g CH4/hd/d between treatments. No significant difference was observed between treatments for daily CH4 production (P=0.95), CO2 production (P=0.95), CH4 as a percent of gross energy (GE) intake (Ym; P=0.87), CH4 yield (MY; g CH4/kg DMI; P=0.80), and CH4 emission intensity (EI; g CH4/kg of BW gain; P=0.70). Similarly, a treatment effect was not observed for DMI (kg/d; P=0.92), average daily gain (ADG; kg BW gain/d; P=0.53), or feed efficiency (G:F; kg of BW gain/kg of DMI; P=0.42). Nitrogen intake ranged from 195 to 214 g/d among treatments (P=0.93). No significant difference was observed among treatments for fecal output (P=0.98), fecal N (FN; P=0.98), fecal neutral detergent fiber (NDF; P=0.33), or fecal acid detergent fiber (ADF; P=0.30). Estimated urine nitrogen (UN) (P=0.77), FN:UN (P=0.93), and N excretion (P=0.86) did not differ among treatments when estimated using methodologies described by Kohn (2005) (Table 5). Similarly, estimated UN (P=0.66), FN:UN (P=0.94), and N excretion (P=0.72) did not differ among treatments when estimated using methodologies described by Reed (2015). Moreover, no significant difference was observed among treatments for serum parameters, blood urea nitrogen (BUN; P=0.99) or creatinine (P=0.20), the common oxidative stress biomarker malondialdehyde (MDA; P=0.63), or antioxidant enzyme biomarkers superoxide dismutase (SOD; P=0.26) and reduced glutathione (GSH; P=0.19). Ultimately, the results of this study would not indicate that low-level tannin supplementation alters CH4 emissions, estimated N excretion, oxidative stress, or animal performance in organic dairy heifers.
Keywords: methane; oxidative stress; tannins; nitrogen; heifers; performance